The relationship between parental health literacy levels and anthropometric measurements of children in Turkey - Ozcan Aygun; Mine Topcu (BMC, 2023)
Abstract Objective The aim of this study was to identify the relationship between parental health literacy levels and anthropometric measurements of children in Turkey. Methods The research was of cross-sectional/correlational design and carried out with 378 consenting parents registered at a Family Health Center. A Sociodemographic Data Form and the Health Literacy Scale for Turkey-32 was used to collect the study data. Data collection was completed at face-to-face interviews held in the consultation department of the family health center. The data were analyzed with the chi-square test and Ordinal Logistic Regression Analysis. Results It was determined that parental health literacy levels were associated with level of education, income status and the state of the parents' employment (p < .05). A relationship was also found between adequate levels of parental health literacy and the health status, weight and height standard deviation scores by age of the parents' children (p < .05). Conclusion This study found that adequate levels of parental health literacy were significantly lower than the European average. The study found that adequate parental health literacy had a positive effect on children's anthropometric measurements. Health institutions and health professionals should plan training programs to improve the health literacy of parents when they apply to health institutions.